#Lorrydeaths: Structural Topic Modeling of Twitter Users' Attitudes About the Deaths of 39 Vietnamese Migrants to the United Kingdom - Than, Nga; Windel, Friederike; Steele, Liza G. (Frontiers in Sociology, 2022)
In this article, we analyze anti- and pro-immigrant attitudes expressed following the Essex Lorry Deaths tragedy in October 2019 in Britain, in which 39 Vietnamese immigrants died in a sealed lorry truck on their way to their destination. We apply Structural Topic Modeling, an automated text analysis method, to a Twitter dataset (N = 4,376), to understand public responses to the Lorry Deaths incident. We find that Twitter users’ posts were organized into two themes regarding attitudes towards immigrants: (1) migration narratives, stereotypes, and victim identities, and (2) border control. Within each theme, both pro- and anti-immigration attitudes were expressed. Pro-immigration posts reflected counter-narratives that challenged the mainstream media’s coverage of the incident and critiqued the militarization of borders and the criminalization of immigration. Anti-immigration posts ranged from reproducing stereotypes about Vietnamese immigrants to explicitly blaming the victims themselves or their families for the deaths. This study demonstrates the uses and limitations of using Twitter for public opinion research by offering a nuanced analysis of how pro-and anti-immigration attitudes are discussed in response to a tragic event. Our research also contributes to a growing literature on public opinion about an often-forgotten immigrant group in the UK, the Vietnamese.